Analisis Minat Belajar Peserta Didik dalam Pembelajaran Tematik Kelas Tinggi SDN 244 Pammana - Wahyu Sriyani Kadir; Sitti Jauhar; Awaluddin Muin (Universitas Negeri Makassar, 2021)
This research is a descriptive qualitative research that aims to determine student’s interest in learning and describe the factors that influence students' interest in thematic learning at SDN 244 Pammana.. The subjects of this research were teachers and students in grades IV, V and VI. There are three teachers and 55 students. Research data obtained from observations, interviews and questionnaires. Data analysis techniques are data reduction, data presentation and drawing conclusion. The results of this research indicate that each indicator consisting of student preparation, feelings of pleasure, engagement, attention and interest of students is good. Factors that influence students' learning interest in thematic learning consist of biological factors, psychological, teacher teaching methods, facilities and infrastructure and the teacher's role. Meanwhile, the inhibiting factors for students' interest in learning consist of learning difficulties for students, friends, family and learning media. Students' learning interest in high grade thematic learning at SDN 244 Pammana Pammana is quite good, but they still need to get attention and guidance from parents and teachers so that they can overcome the inhibiting factors to foster students' learning interest.